Persepsi Mahasiswa terhadap Pembatasan Penggunaan Smartphone di Asrama: Students' Perception of Smartphone Usage Restrictions in Dormitory - Khaerul Aqbar; Azwar, Azwar; Dewi Indriani; Awal Rifai; Mutahharah, Mutahharah (TARBIYAH: Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to measure students' perceptions of the smartphone usage restriction policy implemented by the campus. The research employs a quantitative approach with a survey method and is analyzed using descriptive statistical techniques. The findings indicate that the majority of students hold a positive view of the policy, with most respondents agreeing that it helps them maintain discipline, stay focused on their studies, reduce time spent on less productive activities such as gaming and social media, and enhance their interaction with the campus environment. The policy is also considered effective in supporting better character development among students. The implications of these findings suggest that smartphone usage restrictions can be an effective tool for improving the quality of education and character formation in higher education settings.